A review on the potential of natural and synthetic composites for ballistic resistance - Mohd Pazlin Bin Saion; Mohd Yuhazri Bin Yaakob; Mohd Amirhafizan Bin Husin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2021)
This review evaluates on the concept and essential of bio composite and the synthetic composite fabric positioned over the years from the previous studies. The sorts and features of matrix and fiber filler reinforcement materials in composites also are discussed. The main findings in this review show that the centre of composite relies on the natural fiber against synthetic and the impact of lamination between them. Therefore, the contemporary hybrid compound for synthetic fiber and bio composite fiber in a composite shape is anticipated performing higher in the issue of mechanical energy in particular within the application of high impact, besides decreased dependency on artificial fiber. The table and figure previous results are comparing the experimental parameters available inside the literature review. This paper goes over the present advancement structure and development procedures included and related works on upgrading low and high impact energy captivation and upgrading the mechanical tenacity for high impact resistance applications.